Infestation Of Endometrium By Mycobacterium Tuberculosis Bacilli-Cause Of Reproductive Failure - Rajib Gon Chowdhury , Suman Kalyan Paine, Basudev Bhattacharjee and Siddhartha Chatterjee (Al Ameen Medical College, 2010)
Abstract: Tuberculosis is known to be one of the major diseases, causing infertility in India. The prevalence of tuberculosis causing infertility is different in different countries. Established tubercle infection may cause irreversible infertility, on many occasions as it may affect all the reproductive organs. It also produces lower pregnancy rate in Assisted Reproductive Technology program as well. Tubercular bacillary infestation of the endometrium that is mere presence of Mycobacterium Tuberculosis (MTB) bacilli on the endometrial surface has been found to affect fertility as well. In this study, we have detected Mycobacterium Tuberculosis (MTB) infestation of endometrium, causing implantation failure or early embryonic rejection. In many cases of unexplained infertility, tubercular bacilli infestation of endometrium, has come out to be the root cause of infertility. Association of tubercular bacillary infestation and endometriosis is another cause of concern. Recurrent abortions and ectopic pregnancy may be precipitated by the same genital pathology as well. The presence of very small number of bacilli, which escapes detection by AFB smear, culture or histology, may be detected by polymerase chain reaction techniques. These bacillary infections bring an inflammatory change in the endometrium and produces harmful cytokines which are responsible for implantation failure of micro abortion.